Biosorption study in a mining wastewater reservoir. (17th October 2008) - Naja, Ghinwa; Mustin, Christian; Volesky, Bohumil; Berthelin, Jacques
An in situ sorption was conducted to assess the behaviour of cations in a mining wastewater reservoir. Sorption experiments on test materials showed that biomass mainly bound uranium, copper, lead, zinc, and nickel, whereas goethite bound arsenic and chromium. Clay minerals bound both barium and rare earth elements. The lacustrine sediments mainly contained iron oxy-hydroxides. Desorption experiments using potentiometric titration were conducted to investigate the effect of pH variations on the stability of the test sorbents after immersion in the lake. Results indicated the presence of weak to very weak acidic functional groups in the sediments attributed to their high content of organic matter affecting the mobility and the behaviour of metals in the lake deposits.